Perancangan Sistem Penyewaan Bus Berbasis Laravel Framework PT Sumber Jaya Trans Tangerang - Dzakwan Taqiyyuddin Al Fatah; Sari Safitri; Wahyu Manurian (UNIVERSITAS RAHARJA, 2021)
The need for transportation for the community, especially in Tangerang Regency, which is used for holidays, tours, study tours, or pilgrimage. is a promising business opportunity for transportation companies.Because the need for transportation is important for the smooth running of its activities. PT. Sumber Jaya Trans Tangerang, which is involved in passenger transportation services, is one of the companies engaged in this field. In its operation still uses a manual system in renting buses. Many obstacles occur in this bus rental, such as business processes that have not been computerized, and data storage that is less effective and efficient. The research method in the analysis of the system used is PIECES which consists of Performance, Information, Economy, Control, Efficiency and Service. The system design uses object-oriented analysis method with Unified modeling Language (UML), the programming language used is PHP and the database used is MySQL. This system is web-based and uses the PHP 7 programming language, Web Design with CSS Bootstrap, Laravel Framework and MySQL for database design, while supporting software used in making programs is Visual Studio Code. In this research, a system has features such as master data, transactions, bus schedules, destinations, calendars, transaction reports, road warrant reports and activity logs. With this bus rental system, the bus rental process that is running will be more effective and efficient.